Progressive resisted exercises along with dietary modification on the level of TSH in subclinical hypothyroidism among females with menstrual disorders - Sadbhawna; Sonia Singh; Nitin Gupta (Ethiopian Journal of Reproductive Health, 2024)
Objective:The subclinical hypothyroidism (SCH) and menstrual disorders are the common clinical manifestations affecting women. The management of SCH remains dearth considering it as a mild disorder. However, its consequences keep on splaying silently. There is an ambiguity in literature in context to effect of exercises on the levels of TSH so the present study was designedto identify the effect of Progressive resisted exercises (PRE) along with dietary modification on levels of TSH among females with SCH. Methods: Total 74 females aged 18-35 years suffering from menstrual disorders were recruited. All participants underwent thyroid profile testing (T3, T4 and TSH). The participants with normal T3, T4 and raised TSH (4.6-10µIU/mL) were included and were divided into two groups. The participants in Group A received dietary modification and Group B received PRE along with dietary modification. A protocol of six week was administered to both the groups and levels of TSH were compared with baseline readings after the completion of the protocol. Results: Paired t-test showed a significant improvement in the levels of TSH in both the groups. Further, unpaired t-test revealed that Group B was more effective than Group A. Conclusion: PRE along with dietary modification is an effective protocol for improving the levels of TSH in SCH among females with menstrual disorders. Keywords: Subclinical Hypothyroidism (SCH), Progressive resisted exercises, menstrual disorders.